Les textes francophones malgaches sont-ils hybrides? - Ranaivoson, Dominique (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Francophone literary production in Madagascar, although born out of a colonial context, has found its own voice in terms of the codes and themes it uses. It seeks to take its place in Francophone literature through comprehension based on a common language. However, the works written in French are informed by the cultural, social, spiritual and linguistic context of Madagascar. The resulting texts are full of allusions to prestigious literary genres, shared concerns and concepts whose comprehension is difficult for a readership which understands the words without understanding their cultural connotations. It is necessary to reflect on the specific task of the literary critic who may, whilst respecting the dynamics of a literary text, add annotations in the form of ‘cultural translations’. The aim would be not to smother a body of work, which must be allowed to maintain its own nuances, but to allow better knowledge of the works and to make more effective the intercultural exchanges which are part of contemporary globalisation.